# 99 questions/Solutions/17

### From HaskellWiki

< 99 questions | Solutions(Difference between revisions)

(cleanup) |
Blazedaces (Talk | contribs) (Added another solution) |
||

Line 31: | Line 31: | ||

split xs 0 = ([], xs) |
split xs 0 = ([], xs) |
||

split (x:xs) n = let (f,l) = split xs (n-1) in (x : f, l) |
split (x:xs) n = let (f,l) = split xs (n-1) in (x : f, l) |
||

+ | </haskell> |
||

+ | |||

+ | A similar solution using foldl: |
||

+ | |||

+ | <haskell> |
||

+ | split :: [a] -> Int -> ([a], [a]) |
||

+ | split [] _ = ([], []) |
||

+ | split list n |
||

+ | | n < 0 = (list, []) |
||

+ | | otherwise = (first output, second output) |
||

+ | where output = foldl (\acc e -> if third acc > 0 then (first acc ++ [e], second acc, third acc - 1) else (first acc, second acc ++ [e], third acc)) ([], [], n) list |
||

+ | </haskell> |
||

+ | |||

+ | Note that for the above code to work you must define your own first, second, and third functions for tuples containing three elements like so: |
||

+ | |||

+ | <haskell> |
||

+ | first :: (a, b, c) -> a |
||

+ | first (x, _, _) = x |
||

+ | |||

+ | second :: (a, b, c) -> b |
||

+ | second (_, y, _) = y |
||

+ | |||

+ | third :: (a, b, c) -> c |
||

+ | third (_, _, z) = z |
||

</haskell> |
</haskell> |

## Revision as of 09:01, 16 November 2011

(*) Split a list into two parts; the length of the first part is given.

Do not use any predefined predicates.

Solution usingtake

drop

split xs n = (take n xs, drop n xs)

splitAt

split = flip splitAt

But these should clearly be considered "predefined predicates". Alternatively, we have the following recursive solution:

split :: [a] -> Int -> ([a], [a]) split [] _ = ([], []) split l@(x : xs) n | n > 0 = (x : ys, zs) | otherwise = ([], l) where (ys,zs) = split xs (n - 1)

The same solution as above written more cleanly:

split :: [a] -> Int -> ([a], [a]) split xs 0 = ([], xs) split (x:xs) n = let (f,l) = split xs (n-1) in (x : f, l)

A similar solution using foldl:

split :: [a] -> Int -> ([a], [a]) split [] _ = ([], []) split list n | n < 0 = (list, []) | otherwise = (first output, second output) where output = foldl (\acc e -> if third acc > 0 then (first acc ++ [e], second acc, third acc - 1) else (first acc, second acc ++ [e], third acc)) ([], [], n) list

Note that for the above code to work you must define your own first, second, and third functions for tuples containing three elements like so:

first :: (a, b, c) -> a first (x, _, _) = x second :: (a, b, c) -> b second (_, y, _) = y third :: (a, b, c) -> c third (_, _, z) = z